RUSSIA IN THE FOREIGN POLICY PRIORITIES OF THE COUNCIL OF COOPERATION OF THE ARABIAN GULF STATES AFTER EVENTS OF THE «ARAB SPRING» - E. C. Melkumyan; G. G. Kosach; T. B. Nosenko (Vestnik MGIMO-Universiteta, 2017)
The proposed article focuses on the change in the approach of the regional organization of the Gulf Cooperation Council (GCC) to Russia’s role in the Middle East region and the efforts of its members to establish fruitful cooperation with it. A new approach followed the events of the “Arab Spring”, among which the outcome was a complication of the regional situation and the emergence of a series of crises that forced the members of the GCC to expand the number of allies among the world’s leading powers. Russia’s active participation in resolving crisis situations in the Middle East, primarily in Syria, influenced the change in the GCC policy towards Russia, which realized its increased interest in establishing strong ties with the countries of this region. The article compares the relations that existed between Russia and the GCC states in the Soviet period and the initial period of the Russian Federation’s existence, and those relations that began to develop after 2011 amid growing instability in the Middle East region. A new stage in bilateral relations was caused by the coincidence of their interests in the fight against the increased terrorist threat. The parties were also interested in conducting political consultations to resolve regional crisis situations. The coincidence of points of view between Russia and the GCC on the Middle East settlement has always been a reliable basis for building mutual understanding between the parties. At the same time, the contradictions that arose between them on the issue of ways out of the Syrian crisis led to a cooling in their relations. The authors conclude that the place of Russia in the foreign policy priorities of the GCC is going to grow. The mutual interest of the parties in political interaction is reinforced by the need to coordinate policy in the energy market, the largest suppliers of which are both Russia and the GCC states. In addition, both sides are striving to expand economic and militarytechnical cooperation, which will create a favorable situation for establishing relations in the political sphere.